2018
DOI: 10.1042/bsr20180240
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen attenuates dialysate-induced peritoneal fibrosis by inhibiting GSK-3β/β-catenin axis activation

Abstract: Peritoneal fibrosis is a severe complication arising from long-term peritoneal dialysis (PD). Tamoxifen (Tamo) has been clinically proven effective in a series of fibrotic diseases, such as PD-associated encapsulating peritoneal sclerosis (EPS), but the mechanisms underlying Tamoxifen’s protective effects are yet to be defined. In the present study, C57BL/6 mice received intraperitoneal injections of either saline, 4.25% high glucose (HG) PD fluid (PDF) or PDF plus Tamoxifen each day for 30 days. Tamoxifen att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…They found that inhibiting β-catenin reversed the expression of high-glucose-induced EMT markers. In another study, high-glucose dialysate was reported to induce phosphorylation of glycogen synthase kinase (GSK)-3β and thus inhibit degradation of β-catenin [26]. Ultimately, this β-catenin signaling was implicated in EMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that inhibiting β-catenin reversed the expression of high-glucose-induced EMT markers. In another study, high-glucose dialysate was reported to induce phosphorylation of glycogen synthase kinase (GSK)-3β and thus inhibit degradation of β-catenin [26]. Ultimately, this β-catenin signaling was implicated in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, this β-catenin signaling was implicated in EMT. Yan et al [26] investigated the association between high-glucose dialysate treatment and GSK-3β phosphorylation and demonstrated that tamoxifen downregulated the GSK-3β/β-catenin axis. Kazama et al [27] focused on the function of mast cells in progression of peritoneal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Non-ATP competitive GSK 3β inhibitors, including LiCl, TDZD-8 and L803-mts, could also induce significant inhibition of tumor growth ( 108 ). A previous study has revealed that TWS119 could reverse the effects of tamoxifen on β-catenin and Snail expression thereby inhibiting GSK-3β/β-catenin activation ( 109 ). Furthermore, TWS119 exhibited different effects on CD4 + and CD8 + T cells in tumor-infiltrating lymphocytes (TILs) by stimulating the expansion of naive T cell and CD8 stem cell-like memory T cells, and inducing CD8 + effector T-cell proliferation in TILs ( 110 ).…”
Section: Gsk 3β Inhibitors In Antineoplastic Treatmentmentioning
confidence: 99%
“…Although the exact mechanism of action is not yet fully clear, experimental studies suggest that the anti-fibrotic properties of tamoxifen are mediated through estrogen receptor (ER)-independent pathways [15]. In this direction, in-vitro studies using human peritoneal mesothelial cells have shown that tamoxifen down-regulates the gene expression of connective-tissue-growth-factor and inhibits the collagen synthesis mediated through the transforming-growth-factor-β (TGF-β) pathway [16,17]. In animal models of PD, administration of tamoxifen is shown to ameliorate the progression of peritoneal thickening and improve peritoneal membrane function through inhibition of the process of mesothelial-tomesenchymal transition [18].…”
Section: Discussionmentioning
confidence: 99%